The Relationship Between Parental Involvement and Study Discipline and Academic Achievement in Pancasila Education Among Fourth-Grade Elementary School Students - Vicka Ria Fauziyah; Wahdan Najib Habiby (Journal of Educational Sciences, 2026)
This study was motivated by the importance of Pancasila Education in instilling moral values and character from an early age. Parental attention, in the form of supervision and motivation, is believed to improve students’ study habits; therefore, the relationship between these variables needs to be examined empirically. This study aims to determine the relationship between parental attention and study discipline on the Pancasila Education learning outcomes of fourth-grade elementary school students. The method used is a quantitative approach with a correlational design. The study population consisted of 63 students in the Rangga Warsita Cluster, Delanggu District, using a saturation sampling technique. Data were collected through a Likert scale questionnaire and documentation of odd-semester PAS scores. The results indicate that parental attention and study discipline each have a significant positive relationship with learning outcomes. Simultaneously, both are significantly associated with a 17.5% contribution, while the remainder is influenced by other factors. These findings underscore the importance of the synergy between parental support and student discipline in improving learning outcomes.